1971
DOI: 10.1073/pnas.68.12.2932
|View full text |Cite
|
Sign up to set email alerts
|

Role of 5S RNA in the Functions of 50S Ribosomal Subunits

Abstract: ABSTRACT50S ribosomal subunits from Bacillus stearothermophilus can be reconstituted from their dissociated components, namely a 5S RNA-free protein fraction, a 5S RNA-free 23S ribosomal RNA fraction, and purified 5S RNA. The biological activity of reconstituted particles in polypeptide synthesis is dependent on the presence of 5S RNA. In the absence of 5S RNA, particles are produced that have greatly reduced activity in (a) polypeptide synthesis directed by synthetic, as well as natural, messenger RNA, (b) pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

1973
1973
1999
1999

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(51 citation statements)
references
References 27 publications
4
46
0
1
Order By: Relevance
“…The following bacterial strains were grown in media, as cited by the references, to mid log phase before harvesting: E. coli Al9 [2] …”
Section: Bacterial Strainsmentioning
confidence: 99%
See 2 more Smart Citations
“…The following bacterial strains were grown in media, as cited by the references, to mid log phase before harvesting: E. coli Al9 [2] …”
Section: Bacterial Strainsmentioning
confidence: 99%
“…Ribosomes from wheat germ were prepared as previously described [ 151, whilst Artemia salina ribosomes were a gift from J. Zimmermann. Poly-U directed polyphenylalanine synthesis was measured as previously published [2]. Yeast tRNAPhe was a generous gift from Dr. 0.…”
Section: Preparation Of Ribosomes and Poly-u Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Its presence in the subunit is essential for ribosomal function (8,9), and it is situated near the interface region which is generally considered to be the main functional centre of the ribosome (10).…”
Section: Introductionmentioning
confidence: 99%
“…(c) It was also shown that TYCG can replace uncharged tRNAs at the ribosomal Asite to mediate the stringent-factor-dependent synthesis of pppGpp and ppGpp [37, 381. (d) Reconstitution experiments with B. stearothermopliilus [39] and E. coli [40] 50s ribosomal subunits lacking 5s rRNA revealed, among other deficiencies, a reduction in aminoacyl-tRNA binding to the ribosomal Asite.…”
Section: Discussionmentioning
confidence: 99%